Adaptive And Fault-Tolerant Data Processing In Cloud Environment: Review - et. al., G. Jasmine Christabel, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cloud technology is a modern technique that utilises assets at the edge of both the cloud purpose of providing resources for IoT (Internet of Things) system requests. The highly distributed network design of cloud network edge allows faults to be a common event and condition monitoring has therefore become important. Time-sensitive demands were not strongly regarded by most initial planning and fault-tolerant techniques. This raises the likelihood of latencies that trigger unfavorable results in fulfilling certain demands. The key purpose is to minimize service latency and running costs and to improve the cloud's stability and power.Undoubtedly, the dynamism and strength of the cloud and its services is the most prevailing topic of this entire decade. However, there come huge challenges with this ease of dynamic cloud environments. Cloud is prone to faults and errors; different services behave differently and can generate a series of unexpected errors. Here comes the system ability to handle these errors gracefully, moreover, the actual challenge is to make this handling effective in the long run. The primary concern for maintaining service stability and programme execution of virtual servers is fairly flexible. Failures must be expected and constructively managed to mitigate the failure effect of the virtualization and programme execution.To foresee these errors and undertake sufficient steps before faults start happening, fault tolerance strategies have been used. This report attempts to provide a deeper understanding of the complexities of appropriate fault-tolerant and describes different methods and strategies used during resistance of faults.